THE USE OF MOBILE LEARNING TO ENHANCE LEARNING INNOVATION PASCA PANDEMIC COVID-19 - Memet Casmat; Benny Agus Pribadi (Journal of Learning and Technology, 2022)
This study aims to identify the characteristics, objectives, benefits, advantages and limitations of mobile learning, analyzing opportunities and challenges the use of mobile learning as a learning model during the Covid-19 pandemic as well describes the application of the use of mobile learning in learning in education base. This research is a literature study with a qualitative approach using descriptive-analytic analysis. The research results show that mobile learning as a subset of e-learning has many advantages in facilitating learning process without the limits of time, space and place. Although it has limitations, but mobile learning has a very good opportunity to be utilized on virtual learning during the covid-19 pandemic as an alternative to learning face to face. Tablets, smartphones and laptops can be used as supporting devices in the implementation of mobile learning. In order to be implemented optimally, teacher skills are needed in operating the device and designing teaching materials properly digitally based.